2015
DOI: 10.1021/acs.nanolett.5b01969
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanistic Insights on Na-Ion Storage in Nongraphitizable Carbon

Abstract: Nongraphitizable carbon, also known as hard carbon, is considered one of the most promising anodes for the emerging Na-ion batteries. The current mechanistic understanding of Na-ion storage in hard carbon is based on the "card-house" model first raised in the early 2000s. This model describes that Na-ion insertion occurs first through intercalation between graphene sheets in turbostratic nanodomains, followed by Na filling of the pores in the carbon structure. We tried to test this model by tuning the sizes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
694
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 730 publications
(765 citation statements)
references
References 43 publications
(60 reference statements)
51
694
1
6
Order By: Relevance
“…[ 274,275 ] Yun et al fabricated 2D pyroprotein-based carbon nanostructures from a self-assembled silk protein nanoplate that were used as a carbon platform to investigate the Na-ion storage behaviors for various local carbon orderings. Figure 10 b presents the typical discharge profi les of carbon materials with different degrees of crystalline ordering.…”
Section: Non-graphitic Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 274,275 ] Yun et al fabricated 2D pyroprotein-based carbon nanostructures from a self-assembled silk protein nanoplate that were used as a carbon platform to investigate the Na-ion storage behaviors for various local carbon orderings. Figure 10 b presents the typical discharge profi les of carbon materials with different degrees of crystalline ordering.…”
Section: Non-graphitic Carbonmentioning
confidence: 99%
“…Reproduced with permission. [ 275 ] Copyright 2015, American Chemical Society. f) Calculated Na storage potential in disordered carbon.…”
Section: Non-graphitic Carbonmentioning
confidence: 99%
“…Turning to the anodes, hard carbon is considered as one of the most promising candidates. [7,8] However, it has a low reversible capacity of around 250 mAh/g with a relatively high potential of ~0.28 V vs Na in average, i.e. showing a poorer behavior than graphite anode in Li-ion battery.…”
mentioning
confidence: 99%
“…Through designing low microporous structure and appropriate spacing of carbon layer, the low porosity hard carbon can achieve the high initial Coulombic efficiency of 86.1% and high reversible capacity of 362 mAh g −1 with an improved plateau capacity of 230 mAh g −1 below 0.1 V [181], which provides new insight into high-performance and practicable hard carbon anodes. Ji and co-workers also suggested that the slope region is related to the sodium storage behavior of edges and surface defects of carbon, rather than micropores, and the low-potential plateau region corresponds to the insertion of Na + into carbon interlayers and minor Na + adsorption on pore surfaces [182]. The Na + cations diffusion variation throughout the insertion/extraction processes at low-potential plateau in hard carbon has been measured by Xiao et al (Figure 8b), which provides helpful insight into the stepwise Na + cation insertion/extraction phases and rates in hard carbon materials [183].…”
Section: Carbon-based Materialsmentioning
confidence: 99%